The effectiveness of promotional tools to enhance public awareness towards services provided by Melaka International Trade Centre (MITC) / Liyana Baharudin - Baharudin, Liyana (Faculty of Business and Management, 2007)
Melaka International Trade Centre (MITC) is one of the great places which have organized various functions and events in Melaka. MITC always ensure that they have sufficient advertisement and publicity to enhance customers' awareness. But, MITC want to more ensure either the promotional tools used by the organization such as telemarketing, fax marketing and e-marketing and outdoor marketing is effective or not in order to enhance public awareness towards services provided by MITC. In this study, MITC seems to face several problems especially in ensuring either the promotional tools done by MITC will enhance level of public awareness or the other way round. The objective of this research is to examine whether the promotional tools done by MITC are effective, to determine the most effective promotional tools which may enhance public awareness towards services provided by MITC as well as to identify the level of public awareness towards MITC. In this research, the researcher uses exploratory and descriptive study. More over, the researcher also uses non-probability sampling technique and convenience sampling to obtain sample of convenience elements. The findings related to the promotional tools done by MITC is effective to enhance public awareness, but the organization should give more emphasize to outdoor marketing, since it is the most effective promotional tools which enhance public awareness. The level of public awareness is quite high as well since people are aware and desired to attend or organize event at MITC. They also agreed that they will use MITC services in the future even though they haven't used it before. By doing this research, MITC will alert the factor that increase their effort in the future to have more effective ways to make the public become more aware of what MITC has to offer.